Cordyceps sinensis polysaccharide inhibits PDGF-BB-induced inflammation and ROS production in human mesangial cells. (10th July 2015) - Wang, Ying; Wang, Yan; Liu, Dan; Wang, Wang; Zhao, Huan; Wang, Min; Yin, Hongping
Highlights: Artificial gastric juice was used for obtaining active polysaccharide CPS-F. CPS-F inhibited PDGF-BB-induced inflammation and ROS production via ERK/Akt pathways. CPS-F is a bidirectional regulator of pro-inflammation factors in HMCs. CPS-F may exert its therapeutic effect for the treatment of glomerulonephritis. Abstract: CPS-F, a polysaccharide derived from Cordyceps sinensis, is a potential anti-inflammatory and anti-oxidative agent. We demonstrated that CPS-F not only inhibits platelet-derived growth factor BB (PDGF-BB)-induced intracellular reactive oxygen species (ROS) generation, and up-regulation of tumor necrosis factor-α (TNF-α), TNF-α receptor 1 (TNFR1), and monocyte chemotactic protein-1 (MCP-1), but also acts synergistically in combination with MAPK/ERK inhibitor U0126 and PI3K/Akt inhibitor LY294002. Additionally, up-regulation of pro-inflammatory factors was reversed by use of a combination of CPS-F and NADPH oxidase (NOX) inhibitor diphenyleneiodonium chloride (DPI) or silencing of NOX1. Furthermore, CPS-F prevents the PDGF receptor β (PDGFRβ) promoter activity induced by PDGF-BB in transfected cells and ameliorates increased levels of TNF-α, TNFR1, and MCP-1 when PDGFRβ is silenced, thereby suggesting that CPS-F possesses a bidirectional regulatory function. Our findings suggest CPS-F may exert its therapeutic effect for the treatment of glomerulonephritis related to human mesangial cells (HMCs) through the ERK1/2/Akt pathways.